Aclimatación de plántulas de Epidendrum schomburgkii (Lindl.) C. Shweinf (ORCHIDACEAE) propagadas In Vitro - Vásquez Pinedo, Jim Dickerson (2005)
This dissertation had the following objectives: Establishing the appropriate substrate for acclimatizing in vitro propagated Epidendrum schomburgkii C. Shweinf (ORCHIDACEAE) plantlets, evaluating the effect of three plant growth promoters, and determining the best dosage for balanced foliar fertilizer (NPK-20-20-20) during acclimatization stage. Appropriate substrate for acclimatizing was determined by evaluation plant growth (height) and number of leaves in four treatments: tree fern, (cyathea spp.), coconut husk (Cocos nucifera), “Llangua” (Cybistax sp.) bark, and “Quinilla” (Manilkara bidentata) bark. Best plant growth and number of leaves was obtained in tree fern, followed by coconut husk. Considering plant height and number of leaves as evaluating parameters, best results for plant growth promoter was obtained using 0.01mg/l (100 ppm) Thiamine. Electric Conductivity of 1.6 mS, corresponding to 1.67g/l, of a balanced foliar fertilizer (NPK-20-20-20) show better results for plant development in Epidendrum schomburgkii (lindl.) C. Shweinf. acclimatizing stage. These results showed as an alternative for orchid growers making possible handling plantlets obtained using in vitro culture techniques.